The Petersen graph - Holton, Derek Allan 1941- (Cambridge University Press, 1993)
The Petersen graph occupies an important position in the development of several areas of modern graph theory because it often appears as a counter-example to important conjectures. In this account, the authors examine those areas, using the prominent role of the Petersen graph as a unifying feature. Topics covered include: vertex and edge colourability (including snarks), factors, flows, projective geometry, cages, hypohamiltonian graphs, and 'symmetry' properties such as distance transitivity. The final chapter contains a pot-pourri of other topics in which the Petersen graph has played its part. Undergraduate students will be able to profit from reading this book as the prerequisites are few; thus it could be used for a second course in graph theory. On the other hand, the authors have also included a number of unsolved problems as well as topics of recent study. Thus it will also be useful as a reference for graph theorists.